2009
DOI: 10.1128/aac.00112-09
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of the Nitroimidazo-Oxazine PA-824 on Renal Function in Healthy Subjects

Abstract: The mechanism underlying a dose-dependent, reversible increase in serum creatinine (SC) caused by the administration of PA-824, a novel nitroimidazo-oxazine, was evaluated in 47 healthy male and female volunteers. Subjects were administered either 800 or 1,000 mg PA-824 or matching placebo once daily for 8 days. The following renal function parameters were determined before and during dosing and after a 7-day washout: SC, glomerular filtration rate (GFR; measured as the iohexol clearance), effective renal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 15 publications
3
46
0
Order By: Relevance
“…Moxifloxacin could be of use in the treatment of latent TB (Hu et al, 2008). The combination of 3 months of once-weekly moxifloxacin and rifapentine was as effective as 6 months of isoniazid monotherapy in a mouse model for latent TB (Ginsberg et al, 2009b). A single dose moxifloxacin of up to 800mg was tolerated well but little is known about the long-term tolerability in TB patients.…”
Section: Moxifloxacin and Gatifloxacinmentioning
confidence: 96%
See 1 more Smart Citation
“…Moxifloxacin could be of use in the treatment of latent TB (Hu et al, 2008). The combination of 3 months of once-weekly moxifloxacin and rifapentine was as effective as 6 months of isoniazid monotherapy in a mouse model for latent TB (Ginsberg et al, 2009b). A single dose moxifloxacin of up to 800mg was tolerated well but little is known about the long-term tolerability in TB patients.…”
Section: Moxifloxacin and Gatifloxacinmentioning
confidence: 96%
“…The results of these studies, combined with the demonstrated activity of PA-824 against drug-sensitive and multidrugresistant M. tuberculosis with no influence of serum concentration by coadministration of RIF, INH, PZA in various combinations Ginsberg et al, 2009a), support investigation of this novel compound for the treatment of tuberculosis. Since multiple doses of 1000mg were associated with a moderate, reversible increase in creatinine, Ginsberg et al made a further assessment (Ginsberg et al, 2009b) of the effects of PA-824 on renal function in healthy subjects. The results suggests that PA-824 causes creatinine level to rise by inhibiting renal tubular creatinine secretion and such an effect is considered clinically benign since it has been described for several marketed drugs.…”
mentioning
confidence: 99%
“…In humans, PA-824 has been well tolerated with constant pharmacodynamic parameters when given once daily, with the maximum serum drug level reached about 4-5 h following oral administration [59,67,68].…”
Section: Pa-824 ( Pretomanid)mentioning
confidence: 99%
“…There were initial concerns about the effect of PA-824 on renal function in man. Although it reduces creatinine excretion in a reversible fashion, it does not reduce the glomerular filtration rate and it does not significantly affect any other aspect of renal physiology [Ginsburg et al 2009]. Similar to PA-824, OPC-67683 is a prodrug and requires in vivo metabolic activation [Mukherjee and Boshoff, 2011].…”
Section: Nitroimidazopyransmentioning
confidence: 99%